Gradients Account for the Thresholds for Perceiving Motion and Depth in Observer-Produced Parallax Displays. (April 2019) - Matsushita, Soyogu; Ono, Hiroshi
We examined whether the thresholds of motion and depth perception produced by motion parallax could be specified by the concept of a disparity gradient. We manipulated both the motion parallax amplitude and the angular separation of two dots and calculated the percentages of trials in which participants perceived motion or depth. The results showed that the amplitude of motion parallax for the threshold increased as the separation became larger with the gradients of 0.023, 0.072, and 0.430 for the lower depth, the lower motion, and the upper depth thresholds, respectively. These findings indicate that the gradient is a useful concept to specify the motion and depth thresholds together rather than parallax amplitude alone.